The Uniqueness of rainville techniques - MN, Vyasa Murthy (Journal of All India Institute of Speech and Hearing, 1971)
Rainville techniques viz., Rainville (Rainville 1959) Modified Rainville or SAL (Jerger and Tillman 1960, Jerger 1965) and Modified Rainville (Lightfort, 1960) of determining BC thresholds have several merits over other methods of BC testing. Some of the merits reported by the advocates of these techniques are: (1) These techniques overcome the problem of localization in BC testing; (2); The problems like when to mask, which ear to mask and how much to mask do not arise; and (3) The prescribed ambient noise level for AC testing is also adequate for BC testing as BC thresholds are determined while the ears are covered